2017
DOI: 10.1007/s12041-017-0763-1
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein gene polymorphisms in Turkish native goat breeds

Abstract: Susceptibility to 'scrapie' disease in goats is influenced by polymorphisms of the prion protein (PRNP) gene. The aim of this study was to identify PRNP gene polymorphisms in a total of 356 scrapie disease-free goats from 10 Turkish native breeds. Eighteen single-nucleotide polymorphisms were detected in the caprine PRNP open-reading frame. Ten previously described amino acid substitutions (I142M, H143R, N146S, N146D, R151H, R154H, P168Q, R211Q, Q222K and P240S) and two novel dimorphisms (G134E and Q163P) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Results from our comparisons suggest that geographical origin of the breeds combined with population structure, breeding schemes and scrapie incidence seem to be the key determinants of the PRNP gene profile. Thus, the studied breeds shared similar haplotypic frequencies with many goat breeds reared in neighboring Mediterranean countries, such as certain breeds in Southern Italy (Maltese, Ionica and Red Mediterranean) [ 27 ] and Turkey (Saanen, Akkeci and Kilis) [ 32 ]. However, significant genetic distances were also detected in respect to some other breeds reared in neighboring countries.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Results from our comparisons suggest that geographical origin of the breeds combined with population structure, breeding schemes and scrapie incidence seem to be the key determinants of the PRNP gene profile. Thus, the studied breeds shared similar haplotypic frequencies with many goat breeds reared in neighboring Mediterranean countries, such as certain breeds in Southern Italy (Maltese, Ionica and Red Mediterranean) [ 27 ] and Turkey (Saanen, Akkeci and Kilis) [ 32 ]. However, significant genetic distances were also detected in respect to some other breeds reared in neighboring countries.…”
Section: Discussionmentioning
confidence: 86%
“…The present study confirms that the dairy goat population in Greece, collectively represented here by the three studied breeds, is one of the very few worldwide where all scrapie resistance-associated alleles in the three codons (146, 211 and 222) have been detected. Previous research in Turkey has also reported presence of all these alleles in the goat population; however, much lower frequencies have been reported for alleles 222K and 211Q [ 32 ]. Polymorphic variation in the PRNP gene locus reported in our study enables the design and implementation of breeding programs towards enhanced scrapie resistance in goats reared in Greece.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations